THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITIES ON BRAND LOYALTY - Yulianto, Edy; Purwianti, Lily; jesty, Jesty (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
Social commerce is a concept that combines elements of electronic commerce with social activities that occur on social media platforms. This involves the use of social media to facilitate trading activities, from product promotion, interaction between users, to the purchasing process stage that can be done directly on the platform. This study aims to analyze in depth how Social Media Marketing Activities (SMMA) influence Brand Loyalty (BL) by considering the mediation role of Brand Awareness (BA), Brand Trust (BT), and Brand Image (BI). In the process, this study found that each variable analyzed had a significant impact on other variables. However, there is a variable relationship between Social Media Marketing Activities and Brand Loyalty with Brand Awareness mediation stating insignificant results. This is because there are social media activities that are less relevant, uninteresting, and not in accordance with the preferences of target consumers, so they fail to build strong brand loyalty. To support this analysis, data were collected from 322 respondents over a period of approximately four months. The data obtained were then analyzed using the concept structural equivalence modeling program (PLS-SEM), which allows researchers to examine the complex relationships between the various variables in this research model.